Use of integrated services in antenatal care: A case study of Mabvuku Polyclinic, Zimbabwe - Gamuchirai P. Gwaza; Danai T. Zhou; Annette Plüddemann; Carl Heneghan (African Journal of Primary Health Care & Family Medicine)
Background: The integration of diagnostic services presents a critical opportunity to improve health outcomes in low- and middle-income countries (LMICs), potentially averting up to 1 million premature deaths annually. Antenatal care provides a critical platform for diagnosing multiple diseases in an integrated manner.